Revitalisasi Nilai-Nilai Pancasila Melalui Peran Organisasi Pemuda di Masyarakat - Khoirunnisak, Anis; Agustinus Sutriyanto Hadi (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2023)
The lack of implementation of Pancasila values ​​in people's lives show that there are still many people, especially the young generation, who neglect to apply the values ​​of Pancasila because of the influence of globalization and modernization, so that the revitalization of Pancasila values ​​needs to be done. This research uses interview, observation, and documentation techniques. The results of the study describe three substances, namely: 1) The role of the branch subsidiary Nahdlatul Ulama Student Association (IPNU/IPPNU) in Kabuh Jombang Regency through organizational culture in introduction, training activities and combination organizational culture through activity programs such as: Sholawatan, Istighosah, Millenial Edu Center, CBP/KPP, Makesta, Diklatama, and Lakmud; 2) The results of the revitalization of Pancasila; 3) Supporting and inhibiting factors for cultural revitalization, namely: a) The supporting factor found was community support; b) The inhibiting factor found was internal conflict within the organization..